2019
DOI: 10.3390/insects10060164
|View full text |Cite
|
Sign up to set email alerts
|

RNAi-Mediated Knockdown of Tssk1 and Tektin1 Genes Impair Male Fertility in Bactrocera dorsalis

Abstract: The genetic-based sterile insect technique (SIT) is an effective and environmentally safe strategy to diminish populations of agricultural and horticultural insect pests. Functional characterization of genes related to male fertility can enhance the genetic-based SIT. Tssk1 has been involved to control male fertility in both mammals and insects. Moreover, Tektin1 has also been revealed to influence male fertility in both human and mammals. These findings suggested that Tssk1 and Tektin1 identified from Bactroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 47 publications
2
38
0
Order By: Relevance
“…Knockout of Drosophila testis‐specific lncRNA CR42858 −/− also reduced both the number of spermatozoa and male fertility (Wen et al ., 2016). As was demonstrated in B. dorsalis (Sohail et al ., 2019), the impaired male fertility of Z. cucurbitae was probably due to reduced numbers of spermatozoa, which may represent a deficit in spermatogenesis.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Knockout of Drosophila testis‐specific lncRNA CR42858 −/− also reduced both the number of spermatozoa and male fertility (Wen et al ., 2016). As was demonstrated in B. dorsalis (Sohail et al ., 2019), the impaired male fertility of Z. cucurbitae was probably due to reduced numbers of spermatozoa, which may represent a deficit in spermatogenesis.…”
Section: Discussionmentioning
confidence: 96%
“…This result suggested that these lncRNAs play essential roles in male Z. cucurbitae as they showed relatively high expression in this developmental stage. Similarly, a testis‐specific expressed gene, Tektin1 , was found to be abundantly distributed in both pupa and adult males of Bactrocera dorsalis (Sohail et al ., 2019). In multiple developmental stages of B. mori , the Voe1 gene is only expressed in pupae and adults, and this was specifically expressed within the testis (Xie et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies focussed on the improvement of SIT by silencing genes related to sexual determination or fertility presented positive results for the production of intersex individuals (Salvemini et al., 2009; Sarno et al., 2010), alteration of the reproduction apparatus (Chen et al., 2008; Thongsaiklaing et al., 2018) and reduction in mating rates (Gui et al., 2017, 2018), sperm production and quality (Cruz et al., 2018; Sohail et al., 2019), and number of eggs laid and hatched (Ali et al., 2017; Vannini et al., 2010; Zheng et al., 2015). However, RNAi has been the object of studies in other fields of physiological importance, involving the role of genes related to symbiotic microbiome (Yao et al., 2016), the increase in the susceptibility of fruit flies to insecticides (Huang et al., 2015a; Wang et al., 2017), and the growth and development of larvae and pupae (Li et al., 2017; Xiong et al., 2016; Yang et al., ,2013, 2015).…”
Section: Discussionmentioning
confidence: 99%